Maternal Pre-pregnancy Body Mass Index Categories and Infant Birth Outcomes: A Population-Based Study of 9 Million Mother-Infant Pairs - Zong Xin'nan; Wang Huan; Yang Liu; Guo Yajun J; Zhao Min; Magnussen Costan G; Xi Bo (FRONTIERS MEDIA SA, 2022)
Background and aims: Infant adverse birth outcomes have been suggested to contribute to neonatal morbidity and mortality and may cause long-term health consequences. Although evidence suggests maternal prepregnancy body mass index (BMI) categories associate with some birth outcomes, there is no consensus on these associations. We aimed to examine the associations of maternal prepregnancy BMI categories with a wide range of adverse birth outcomes.
Methods: Data were from a population-based retrospective cohort study of 9,282,486 eligible mother-infant pairs in the U.S. between 2016 and 2018. Maternal prepregnancy BMI was classified as: underweight (<18.5 kg/m2); normal weight (18.5-24.9 kg/m2); overweight (25.0-29.9 kg/m2); obesity grade 1 (30-34.9 kg/m2); obesity grade 2 (35.0-39.9 kg/m2); and obesity grade 3 (≥40 kg/m2). A total of six birth outcomes of the newborn included preterm birth, low birthweight, macrosomia, small for gestational age (SGA), large for gestational age (LGA), and low Apgar score (5-min score <7).
Results: Maternal prepregnancy overweight and obesity increased the likelihood of infant preterm birth, with odds ratios (ORs) (95% CIs) of 1.04 (1.04-1.05) for overweight, 1.18 (1.17-1.19) for obesity grade 1, 1.31 (1.29-1.32) for obesity grade 2, and 1.47 (1.45-1.48) for obesity grade 3, and also for prepregnancy underweight (OR = 1.32, 95% CI = 1.30-1.34) after adjusting for all potential covariates. Prepregnancy overweight and obesity were associated with higher odds of macrosomia, with ORs (95% CIs) of 1.53 (1.52-1.54) for overweight, 1.92 (1.90-1.93) for obesity grade 1, 2.33 (2.31-2.35) for obesity grade 2, and 2.87 (2.84-2.90) for obesity grade 3. Prepregnancy overweight and obesity was associated with higher odds of LGA, with ORs (95% CIs) of 1.58 (1.57-1.59) for overweight, 2.05 (2.03-2.06) for obesity grade 1, 2.54 (2.52-2.56) for obesity grade 2, and 3.17 (3.14-3.21) for obesity grade 3. Prepregnancy overweight and obesity were also associated with higher odds of low Apgar score, with ORs (95% CIs) of 1.12 (1.11-1.14) for overweight, 1.21 (1.19-1.23) for obesity grade 1, 1.34 (1.31-1.36) for obesity grade 2, and 1.55 (1.51-1.58) for obesity grade 3.
Conclusion: Our findings suggest maintaining or obtaining a healthy body weight for prepregnancy women could substantially reduce the likelihood of important infant adverse birth outcomes.